The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/0895904812468227
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Equity for “Minoritized” Students

Abstract: Using critical policy analysis focused on racial-ethnic equity, this study analyses state policy documents and accountability instruments governing transfer from 2-year colleges to 4-year institutions in the following states: California, Florida, Texas, Michigan, Minnesota, Washington, and Wisconsin. Based on data collected in 2009, the findings indicate that state transfer policies are largely “color blind.” In contrast, accountability reporting, including data indicators such as those for underrepresented st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Some reformers have recommended community colleges transform institutional culture from taking a “cafeteria style” approach to curricula to offering highly structured pathways that allow students to more easily navigate programs and complete credits with greater alignment to their educational goals, including transfer (Bailey et al 2015). Institutional culture is also about a focus on promoting equity in transfer student outcomes, given that most state policy in transfer is “race-blind” (Chase et al 2014) and rarely prioritizes transfer for socioeconomically disadvantaged students. Although not discussed by Jain et al (2011), 4-year institutional culture also varies in terms of the value and respect given to community colleges, and specifically whether community college courses are perceived to be equivalent in content and rigor to courses at the 4-year.…”
Section: Institutionsmentioning
confidence: 99%
“…Some reformers have recommended community colleges transform institutional culture from taking a “cafeteria style” approach to curricula to offering highly structured pathways that allow students to more easily navigate programs and complete credits with greater alignment to their educational goals, including transfer (Bailey et al 2015). Institutional culture is also about a focus on promoting equity in transfer student outcomes, given that most state policy in transfer is “race-blind” (Chase et al 2014) and rarely prioritizes transfer for socioeconomically disadvantaged students. Although not discussed by Jain et al (2011), 4-year institutional culture also varies in terms of the value and respect given to community colleges, and specifically whether community college courses are perceived to be equivalent in content and rigor to courses at the 4-year.…”
Section: Institutionsmentioning
confidence: 99%
“…They recommended adjustments to the scoring rubric to lessen the impact of teaching context on the outcome. Chase, Dowd, Pazich, and Bensimon (2014) included an action research element to their CPA, which focused on issues of racial and ethnic equity in state policies regarding transfer from community colleges to 4-year state…”
Section: Framework: Critical Approaches In Education Policy Analysismentioning
confidence: 99%
“…Strategic planning tends to be assumed as an objective process that produces rational solutions, but research has demonstrated how seemingly objective, apolitical, and well-intentioned policies and policy tools, such as strategic planning, are riddled with subjectivity and political influences that can have disparate impacts on different student groups (Chase, Dowd, Pazich, & Bensimon, 2014;Dowd & Bensimon, 2015;Marcus, 1999). For example, Chase and associates (2014) examined transfer policies in seven states and found that because transfer policies are largely color blind and uncritical, they perpetuate existing racial inequities.…”
Section: Research On Strategic Planning In Higher Educationmentioning
confidence: 99%
“…Traditional policy research, however, also tends to assume objectivity and is uncritical of the value-laden and political nature of policy creation, the complexity of implementation, or the social construction of policy problems (Alemán, 2007;Honig, 2006;Iverson, 2007). The lack of critical research in educational policy studies has resulted in little research examining how seemingly "neutral" educational policies reinforce inequities, whether through the planning process, practitioner sense-making of policies, the implementation of strategic plans, or the effects on different student groups outcomes (Chase, 2016;Chase, Dowd, Pazich, & Bensimon, 2014;Iverson, 2007). A critical lens to policy analysis is needed to examine how equity planning differs from strategic planning particularly in addressing the equity gaps experienced by historically disadvantaged student groups.…”
Section: An Equity Planning Approach In California's Community Collegesmentioning
confidence: 99%
See 1 more Smart Citation